Effect of hydrocarbon addition on tip opening of hydrogen-air bunsen flames. (27th January 2021) - Prasad, T. Guru; Jithin, E.V.; Varghese, Robin John; Kumar, Sudarshan; Mohammad, Akram; Velamati, Ratna Kishore
Abstract: The effect of hydrocarbon addition on tip opening of lean and stoichiometric hydrogen-air flames is studied computationally by performing two-dimensional numerical simulations. The numerical study reveals that the flame tip of the H2 -air burner stabilized flame is open at lean and stoichiometric mixture conditions. The flame tip closes upon hydrocarbon addition. The tip closing is mainly affected by preferential diffusion of the multi-component mixture and the stretch effects. In the addition of light hydrocarbon (CH4 ), the tip closing starts at a higher percentage of hydrocarbon addition in H2 -air flames. Whereas, upon the addition of heavy hydrocarbons such as propane and butane in H2 -air flames, tip closing starts with a lesser amount of hydrocarbon addition. Temperature, OH mole fraction and heat release rate have been investigated, focusing on the flame structure at the tip. The tip opening regime diagram for H2 –CH4 -air, H2 –C3 H8 -air and H2 –C4 H10 -air mixtures are presented. Highlights: Effect of hydrocarbon addition on the tip opening of H2 -air flames is studied. Addition of hydrocarbon increases the intensity of burning at the tip. Tip opening is strongly depended on preferential diffusion for HC-H2 -air flames. Tip closing occurs earlier by adding higher hydrocarbons compared to CH4 addition. Tip opening regime is presented for lean and stoichiometric HC-H2 -air flames.